Impact of microfinance on the efficiency of maize producers in North Eastern Nigeria - Auwal, Ahmed Muhammad (2017)
Access to credit is vital in agricultural production due to low income from both farming and non-farm undertakings and this impedes investing in production inputs especially among smallholder farmers. These farmers produced about 90% of the total food supply, but the production has been declining over the last few years due to lack of funding, a situation that subjects them to low efficiency, low output and income which aggravates poverty in the country. Microfinance as an alternative means of providing financial services to the poor, have the potential to increase their income which if well spend on farm inputs could eventually increase their well-being. The main objective of the study was to determine the impact of microfinance credit towards efficiency and net income improvement as well as the well-being of the beneficiaries. To examine the impact precisely, a group of non-credit beneficiaries was also studied. The impact was determined by comparing two groups of maize producers namely, credit beneficiaries (CB) and non-credit beneficiaries (NCB). The study also analyzed the socio-economic and maize farm related factors influencing technical inefficiency in the farming practices. Data were collected from 600 respondents using stratified random sampling technique in four states which include; Adamawa, Bauchi, Gombe and Taraba based on their prominence in maize production activities. A well-designed questionnaire was used as an instrument to gather information and data. Descriptive and inferential statistics such as slacks-based measure of efficiency model, slacks-based super efficiency model, fractional regression model, T-test analysis, net income analysis and Cobb-Douglass production function model were used to achieve the stated objectives. The results indicated that there is a significant difference among the production inputs used by CB and NCB at 1% and 5% levels of probability. Besides, CB have higher maize yield (772.55kg/ha), higher net farm income ($174.47) and a higher technical efficiency scores than their NCB counterparts. The mean technical efficiency of both CB and NCB were 79% and 69% respectively, which implied that the farmers can still improve their respective efficiency levels by about 21% and 31% with the existing technology. The results also indicated that CB received an average daily income of $3.60, while NCB received only $1.34 per day. This implied that the daily income of CB have increased from less than $1.25 per day to about $3.55 per day as a result of microfinance credit. According to the study, about 38 (CB) and 22 (NCB) farmers were super-efficient. The super-efficiency scores describe those farmers that applied inputs in an appropriate quantities during the production process and hence, were well represented by high input-output ratios. Super-efficiency scores of greater than one distinguish the best performing farmers from the worst and these farmers represent the most important ones that are extremely efficient. Microfinance credit, household size, years of farming experience, extension contact and education increased technical efficiency, while off-farm activities, drought and age decreased technical efficiency in maize farming. Costs of labour, cost of seeds, cost of agrochemicals and cost of fertilizer were found to have negative effect on net income of the farmers. Based on the findings, it can be concluded that the higher technical efficiency, higher output and net farm income levels achieved by CB was due to the presence of microfinance credit which enabled them to purchase more production inputs at the appropriate time than their NCB counterparts. There is need for the extension workers to organize training and workshops in order to disseminate information that can encourage farmers (NCB) to collect microfinance credit in order to expand their scale of operations since it is evident that credit has positive impact on the technical efficiency, net farm income and the well-being of borrowers. Thus, government in collaboration with research institutes and universities should educate farmers on the recommended amount of inputs to apply on their farm lands. This can help them to reduce inputs wastage and production costs thereby increasing their income. It is also very important for government to drill boreholes for the rural farmers in their farm centers so that they can explore avenues for irrigational farming system instead of relying on rainfall for production. This can avert the impact of drought on crops and widens their opportunities to plant at least four times per annum and even diversify to other farming enterprises.